PERBEDAAN KADAR GLIAL FIBRILLARY ACIDIC PROTEIN GFAP SERUM STROKE ISKEMIK DAN HEMORAGIK FASE AKUT BERDASARKAN AWITAN DAN TINGKAT KEPARAHAN STROKE - Alfirdian Irwan,* Syarif Indra,* Yuliarni Syafrita* (NEURONA, 2016)
INTRODUCTION SOME STUDIES HAVE FOUND THAT GLIAL FIBRILLARY ACIDIC PROTEIN GFAP HAS A HIGH DIAGNOSTIC VALUE IN DIS TINGUISHING ISCHEMIC IS AND HEMORRHAGIC STROKE ICH HOWEVER NO STUDIES DIRECTLY COMPARE THE DIFFERENCES IN THE LEVELS OF SERUM GFAP ON THE ONSET AND SEVERITY OF BOTH TYPES OF STROKE